1995
DOI: 10.1021/ja00117a010
|View full text |Cite
|
Sign up to set email alerts
|

Osmium-Promoted Dipolar Cycloadditions with Pyrroles: An Efficient, Stereoselective Synthesis of 7-Azanorbornanes

Abstract: A series of 7-azabicyclo[2.2.l]hept-5-ene complexes are prepared from [0s(NH3)5(q2-L)l2+ (L = pyrrole, 1-methylpyrrole, 2,5-dimethylpyrrole, 1,2,5-trimethylpyrrole, or 1-(trimethylsily1)pyrrole) and various dipolarophiles (e.g., acrylonitrile, methyl acrylate, a-methylene-y-butyrolactone, dimethyl maleate, dimethyl fumarate, N-phenyl maleimide, cyclopentene-1,2-dicarboxylic acid anhydride, and (E>-and (a-methyl 3-(3'-pyridyl)acrylate). The cycloaddition is promoted by coordination of the pyrrole with [Os(NH&]*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
53
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 0 publications
3
53
0
Order By: Relevance
“…Scheme 19) from substituted pyrroles and olefins superficially looks like a Diels-Alder reaction, however, as has been shown in section II.C.1, it is in fact a 1,3-dipolar [3+2] cycloaddition. 356,357 Investigations on the influence of coordinated metal fragments on the reactivity of "remote", uncoordinated 1,3-diene moieties in cycloaddition reactions have been performed by several groups. Vogel, Roulet, et al [595][596][597][598][599] have prepared extensive series of stereochemically well-defined mono-and bis-metalcoordinated complexes of (poly)cyclic polyenes with exocyclic s-cis-butadiene groups, such as 371-373.…”
mentioning
confidence: 99%
“…Scheme 19) from substituted pyrroles and olefins superficially looks like a Diels-Alder reaction, however, as has been shown in section II.C.1, it is in fact a 1,3-dipolar [3+2] cycloaddition. 356,357 Investigations on the influence of coordinated metal fragments on the reactivity of "remote", uncoordinated 1,3-diene moieties in cycloaddition reactions have been performed by several groups. Vogel, Roulet, et al [595][596][597][598][599] have prepared extensive series of stereochemically well-defined mono-and bis-metalcoordinated complexes of (poly)cyclic polyenes with exocyclic s-cis-butadiene groups, such as 371-373.…”
mentioning
confidence: 99%
“…Thus for instance, the reactions of certain 1-alkylpyrroles with nitrileimines have been demonstrated to give pyrrolo-fused pyrazoles [512,513], whereas intramolecular cyclization of nitrile oxide functionalities onto pyrroles involved unstable pyrrolofused isoxazole adducts that underwent ring opening of the isoxazole ring [514]. It has also been established that a series of osmium pyrrole complexes, for example 320 [Os (II)¼[Os(NH 3 ) 5 ](OTf) 2 ], participate as dipoles in cycloadditions with alkenes, for instance providing the endo-adduct 321 in good yield along with minor amounts of the exo-isomer (Scheme 4.96) [515,516].…”
Section: Cycloaddition Reactionsmentioning
confidence: 99%
“…It is reported that cycloaddition reactions of pyrroles with alkenes are limited by the inherent thermodynamic instability of the cycloadducts wherein cycloreversion or retro-Mannich reactions (followed by rearomatization) are predominant. 1517 When we treated pyrrole 14 with maleimide 3 , in toluene at 60 °C as shown in Scheme 5, we observed no cycloadducts from these reactants. However, we did obtain a small amount of adduct that arose from maleimide 3 and a furan-containing contaminant that was present in our commercial sample of 14 , which we determined to have an empirical formula of C 19 H 19 NO 3 from mass spectral analysis.…”
mentioning
confidence: 91%
“…However, as previously mentioned, cycloadducts of pyrroles with dienophiles are inherently thermodynamically unstable. 1517 Osmium complexation of pyrroles has allowed the production of cycloadducts with maleimides and other dienophiles; however, decomplexation is not straightforward and stable cycloadducts can only be isolated after reduction of the resulting dihydropyrrole. 15 The greater aromatic character of pyrroles, as compared with furans or thiophenes, limits their reactivity towards cycloaddition reactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation